Theoretical analysis of non-Newtonian blood flow in a microchannel. (July 2020) - Tanveer, Anum; Salahuddin, T.; Khan, Mair; Malik, M.Y.; Alqarni, M.S.
Highlights: Nanoparticle phenomena has been highlighted. Electroosmotic flow is considered of Bingham fluid. Mathematical peristaltic flow on Bingham Nanofluid. Walls are assumed to be flexible. Exact and analytical solutions are presented. Abstract: Background: In this work the theoretical analysis is presented for a electroosmotic flow of Bingham nanofluid induced by applied electrostatic potential. The linearized Poisson-Boltzmann equation is considered in the presence of Electric double layer (EDL). A Bingham fluid model is employed to describe the rheological behavior of the non-Newtonian fluid. Mathematical formulation is presented under the assumption of long wavelength and small Reynolds number. Flow characteristics are investigated by employing Debye-Huckel linearization principle. Such preferences have not been reported previously for non-Newtonian Bingham nanofluid to the best of author's knowledge. Method: The transformed equations for electroosmotic flow are solved to seek values for the nanofluid velocity, concentration and temperature along the channel length. Results: The effects of key parameters like Brinkmann number, Prandtl number, Debey Huckel parameter, thermophoresis parameter, Brownian motion parameter are plotted on velocity, temperature and concentration profiles. Graphical results for the flow phenomenon are discussed briefly. Conclusions: Non-uniformity in channel as well as yield stress τ 0 cause velocity declaration for both positive and negative values of U . Nanofluid temperature is found an increasing function of electro osmotic parameter κ if U is positive while it is a decreasing function if U is negative. A completely reverse response is seen in case of concentration profile. The thermophoresis parameter Nt, the Brow nian motion parameter Nb and Brinkman number Br cause an enhancement in temperature. The results are new in case of U .